Optimization of Slitlike Carbon Nanopores for Storage of hythane Fuel at Ambient Temperatures - Kowalczyk, Poitr; Bhatia, S. (American Chemical Society, 2006)
Carbons with slitlike pores can serve as effective host materials for storage of hythane fuel, a bridge between the petrol combustion and hydrogen fuel cells. We have used grand canonical Monte Carlo simulation for the modeling of the hydrogen and methane mixture storage at 293 K and pressure of methane and hydrogen mixture up to 2 MPa. We have found that these pores serve as efficient vessels for the storage of hythane fuel near ambient temperatures and low pressures. We find that, for carbons having optimized slitlike pores of size H = 7 Å (pore width that can accommodate one adsorbed methane layer), and bulk hydrogen mole fraction g0.9, the volumetric stored energy exceeds the 2010 target of 5.4 MJ dm-3 established by the U.S. FreedomCAR Partnership. At the same condition, the content of hydrogen in slitlike carbon pores is =7% by energy. Thus, we have obtained the composition corresponding to hythane fuel in carbon nanospaces with greatly enhanced volumetric energy in comparison to the traditional compression method. We proposed the simple system with added extra container filled with pure free/adsorbed methane for adjusting the composition of the desorbed mixture as needed during delivery. Our simulation results indicate that light slit pore carbon nanomaterials with optimized parameters are suitable filling vessels for storage of hythane fuel. The proposed simple system consisting of main vessel with physisorbed hythane fuel, and an extra container filled with pure free/adsorbed methane will be particularly suitable for combustion of hythane fuel in buses and passenger cars near ambient temperatures and low pressures.